Planificación estratégica y su posicionamiento en el mercado de la Empresa Almacenes León de la Ciudad de Riobamba - Aynaguano Llanga, Carlos Alexander (2024)
Abstract: This study focuses on the strategic planning and its positioning in the market of the Almacenes León Company, located in the City of Riobamba. Strategic planning is a crucial process that guides the organization's actions toward achieving its long-term goals, while market positioning determines how consumers perceive the brand in comparison to its competitors. The importance of this issue lies in Almacenes León's need to remain competitive and relevant in a constantly changing business environment. The study analyzes the strategic planning process of Almacenes León, including the formulation of the vision, mission and business objectives, as well as the identification of key strategies to achieve them. Additionally, it examines how these strategies translate into concrete actions to improve the company's market positioning Qualitative and quantitative research methods were used to collect relevant data, such as interviews with management, customer surveys, and analysis of financial data. The findings of this study provided valuable information and it was determined that the hypothesis is positive since strategic planning affects the market positioning of the León warehouse company in the city of Riobamba. The results obtained are essential to identify areas of improvement and develop strategic planning that drives the continued success of the company in the market of the City of Riobamba. Keywords: positioning, marketing, strategies, sales.